Does a green tax impact a heavy-polluting firm's green investments?. Issue 2 (8th January 2022) - Cheng, Bo; Qiu, Baoyin; Chan, Kam C.; Zhang, Hongxia
ABSTRACT: By leveraging the quasi-natural experiment of the passage of the Environmental Protection Tax Law in late 2016 in China that imposed a pollution tax (green tax) on firms, we examine the impact of this tax on the green investments of heavy-polluting firms. Our difference-in-differences results show that the green tax enhances green investments of heavy-polluting firms. Specifically, firm-level green investments of heavy-polluting firms increased by approximately 38% after the green tax than before the green tax relative to an average firm. The findings are robust to a propensity score matching method, fixed-effects models, placebo tests, dynamic effect analysis, and after excluding alternative explanations. Additional analysis suggests that the positive effect of the green tax on green investments is more pronounced for large firms, state-owned firms, and firms with high analyst following. Collectively, we find a green tax policy contributes to green investments.